INDIGENOUS KNOWLEDGE OF MADE IN JAVA WITH SUSTAINABLE ZERO WASTE CONCEPT FROM TULISAN.COM - Reza Akbar; Munadhil Abdul Muqsith; Kusumajanti (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
This study examines the development and implementation of zero-waste-based eco-friendly products as an innovative solution to address environmental challenges resulting from increased waste and resources consumption. The background of this study is based on the urgency of mitigating the impacts of climate changes and environmental degradation, which highlights the need for a sustainable approach in the product life cycle. The main objectives of the study are to analyze the technical and economic feasibility of zero-waste-based eco-friendly products, as well as to evaluate their potential acceptance in the market. The research method used is an extensive literature study. This approach involves collecting, analyzing and synthesizing data from various academic sources such as scientific journals, books, research reports, and other relevant publications that discuss the concept of eco-friendly, products, zero waste, product life cycle analysis, and consumer behaviour towards sustainable products. In this study, the case will be linked to the theory of sustainable development by Jianming Yang. The main findings of this study indicate that eco-friendly products based on zero waste have significant potential reducing carbon footprints, upcycling materials, avoid chemical process that harms environment, avoid method that can harm animal or nature and solid waste volume. The conclusion of this study confirms that the development of eco-friendly products based on zero waste is not technically feasible and ecologically profitable, but also has a promising market share along with the increasing environmental awareness of consumers.